Managing Urban Heritage: Harmonizing Community Uniqueness and Urban Planning in Pasuruan City - Rozuli, Ahmad Imron; Susanti, Anik; Purba, Dano; Kusuma, Adhinugraha Wirayudha; Renwarin, Ryan (SAMPURASUN, 2025)
This research examines Pasuruan City as a cultural heritage landscape shaped by colonial, Islamic, and multi-ethnic layers that continue to color the dynamics of its urban space. The research aims to identify how this heritage is interpreted and integrated into tourism development while uncovering the obstacles that arise in the preservation process and community participation. A qualitative method with an ethnographic approach was employed, utilizing participatory observation, in-depth interviews, and analysis of archives and policy documents. Research subjects included local residents, cultural actors, and local government representatives directly involved in heritage management. The data were analyzed using thematic interpretation to understand the interconnections between historical narratives, urban spatial patterns, and tourism practices. The findings indicate that Pasuruan displays a cultural palimpsest, where colonial buildings, religious sites, and multicultural areas intertwine to form a distinctive urban identity. However, the fragmentation of heritage asset ownership, weak management, and the absence of a connecting narrative between clusters remain major obstacles. In conclusion, a multi-stakeholder strategy is necessary, involving the government, communities, and cultural asset owners, to enable heritage to serve a dual function: as a pillar of collective memory and as a driver for sustainable tourism and the city's creative economy.